Islam And Nationalism In Indonesia: Kh Maimun Zubair's New Interpretation In Tafsir Safinah Kalla Saya'lamun - Fuadi, Muhammad Ali; Vijay Asyfa Betay Seer; Raden Kurnia Kholiska; Mohammad Abdul Aziz; Henki Desri Mulyadi (International Journal of Sociology of Religion, 2024)
This article discusses the relationship between Islam and nationalism in Indonesia, highlighting the important role of Islam in maintaining the integrity of the Republic of Indonesia through the spirit of nationalism. The combined power of religion and nationalism is a strong foundation to unite a diverse nation. This struggle does not only come from nationalists, but also from religious figures, one of whom is KH Maimun Zubair. He often voiced the importance of the national spirit in his lectures, in line with his work in politics through the United Development Party (PPP). This research uses the literature method with an analytical descriptive approach and the sociology of knowledge as an analytical tool. The main focus is the tafsir Safinah Kalla Saya'lamun Fi Tafsir Syaikhina Maimun, by his student Ismail al-Ashcholy, which summarizes the study of Tafsir al-Jalalain. KH Maimun Zubair asserts that nationalism is formed through the bonds of long residence, ethnic mixing, and migration, reflecting the principle of unity without discrimination, as taught since the time of the Prophet. According to him, all humans are equal in the eyes of Allah, and the only difference is the level of piety.